A Simple and Inexpensive Stereotactic Guidance Frame for MRI-Guided Brain Biopsy in Canines. (18th May 2014) - Squires, Alexander D.; Gao, Yabiao; Taylor, Sean F.; Kent, Marc; Tse, Zion Tsz Ho
Abstract : A magnetic resonance imaging (MRI) guided stereotactic system was developed to provide veterinarians a method to accomplish minimally invasive stereotactic brain biopsies and procedures involving the cerebrum in canines. While MR-guided procedures are prevalent for humans, they are less common in animal practices. The system was designed to minimize fabrication costs in an effort to make such procedures more accessible in the veterinary field. A frame constrained the head without the need for punctures and supported registration and guidance attachments. Location data for registration and relevant structures were selected by the clinician, and a reverse kinematic analysis program generated the settings of the stereotactic arch to guide a needle to the desired location. Phantom experiments and three cadaver trials showed an average targeting error of <3 mm using the system.